Gramática: reflexões sobre um percurso de elaboração de manuais - Neves, Maria Helena de Moura [UNESP] (My University, 2011)
As part of a round table entitled “Construction of descriptive grammars”, with authors of descriptive grammars of the Portuguese language, this text presents a personal refl ection that seeks to recover the key issues that have challenged me in this kind of work. In order to do this, I recover the historical route of the decisions I took in the construction of two manuals of Portuguese grammar and, at the same time, I gather, in other works I have written, information that can explain the guidelines adopted. Being consistent with my background and with my praxis, I offer some thoughts towards the fundamental proposition I have always considered such works to have, which is the school destination, something I can summarize in the question of what should constitute a work with the “grammar” at school.

Como parte que é de uma mesa denominada “Construção de gramáticas descritivas”, composta por autores de gramáticas descritivas de língua, este texto apresenta uma reflexão pessoal que busca recuperar as questões centrais que me têm desafiado na execução desse tipo de tarefa.. Para isso, faço um percurso histórico da defi nição dos rumos que segui na construção de dois manuais de gramática da língua portuguesa, e paralelamente recolho, em outras obras que elaborei, indicações que podem explicitar as diretrizes tomadas. Por um vezo de formação e de atuação, dirijo as reflexões para a destinação central que sempre pensei para essas obras, que é a destinação escolar, algo que posso resumir em uma busca de entender o que deva constituir um trabalho com a “gramática”, na escola.
Keywords: Descriptive grammars; Usage Grammar; Grammar at school; Gramáticas descritivas; Gramática de usos; Gramática na escola